FORMULASI DAN EVALUASI SEDIAAN MASKER SHEET EKSTRAK ETANOL DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) - Verawaty Verawaty; Novita Sulimar; Irene Puspa Dewi (Jurnal Ilmiah Manuntung, 2020)
The research was conducted on ethanol extract formulation of red betel leaves (Piper crocatum Ruiz & Prav.). This research aims to formulate the ethanol extract of red betel leaves (Piper crocatum Ruiz & Prav.) to be a dosage of good, effective, and safe sheet mask to use. This research was experimental, in which 12 women aged 18-25 years old were selected to test for irritation that was observed on the skin behind the ear. To test the effectiveness, the observed dosage was facial skin moisture in the T. The results obtained are in the form of an essence that is slightly thick, brown in color, having a distinctive smell of red betel leaf extract, homogeneous, and safe for the skin. For the effectiveness, the test showed that the sheet mask of red betel leaf extract in formula 1 (1%), formula 2 (3%) and formula 3 (5%) were able to increase facial skin moisture. The analysis results showed that there was a significant difference in the average measurement of water content on the volunteers' facial skin of 0.01 (α <0.05).